RECURRENCE OF ORAL CANCER FOLLOWING TREATMENT IN AN INSTITUTIONAL SET UP - A RETROSPECTIVE ANALYSIS OF THE ASSOCIATED FACTOR - Sundara Murthy, Sindhu Priya Kuppusamy; N, Mahathi; Suresh, (International Journal of Psychosocial Rehabilitation, 2019)
Incidence of cancers of the oral cavity is increasing and has replaced laryngeal cancer as the most frequently occurring cancer in the head and neck area. Routine follow up is must for a period of 6 months to 1 year after treatment. Current guidelines advocate a follow-up period of at least 5 years to evaluate the time of recurrence following the treatment of oral cancer. Data samples required for study were taken from hospital records. All the collected data were cross verified and compiled together in an excel sheet. Compiled data were statistically analysed in SPSS software. In this study, a total of 51 patients with oral cancer had undergone treatment. 74.51% of patients reported back without any recurrence after a follow-up period of 6 months to 1 year. On associating recurrence with age it was noted that the recurrence was more in higher age groups p value of 0.025. Recurrence was common in males than females with p value of 0.025 (